Peningkatan Konsentrasi Bekerja Melalui Brain Gym dan Ice Breaker pada Karyawan - Meiwinda, Eka Rizki; Fadhli, Muhammad; Br. Kalit, Vania Christosye (Jurnal Gotong Royong, 2024)
These intervention was carried out on employees of PT. P. The assessment results show that employees such as Seed Production Unit employees have concentration that needs to be improved. After investigating, several causes of concentration problems among employees include visual distraction, auditory distraction, work overload which results in employee fatigue, and demotivation. Then the intervention is in the form of providing a brain gym with several movements that can increase concentration including sipping water, cross crawl, neck rolls, thinking caps, brain button, arm and leg activation, back cross crawl, gravity glider, calf pump, hooks up and ice breaker which trains employee focus for work. The intervention carried out provided significant results in reducing errors in counting sprouts made by employees. This also shows that employee concentration has increased significantly.